The role of incentives and occupational safety and health program in enhancing employee's performance among private sector in Senawang / Shazleen Hamzah - Hamzah, Shazleen (Faculty of Business and Management, 2018)
Employee performance is crucial since it may affect the organization productivity and growth. Performance also as a key in nowadays work environment rather than gender, race or religion. Besides, Safety and Health program that practice in the workplace may contribute to employee performance. This research is to investigate the role of incentives and occupational safety and health program in enhancing employee's performance among Private Sector in Senawang. The independent variable for this research is promotions, rewards, moral incentives, efficiency of incentive system and occupational safety and health program. Meanwhile, questionnaires were used as a method by the researcher for collecting data from the respondent. Based on the findings, only Moral Incentive have significant impact on employee performance in Private Sector at Senawang. Therefore, Private Sector in Senawang needs to consider these factors and provide best solutions to enhance employee performance in the organizational.